MODEL OF HIGHER EDUCATION PERFORMANCE BASED ON TOTAL QUALITY HUMAN RESOURCE MANAGEMENT (TQHRM) AND KNOWLEDGE STRATEGY - Kusnendi, Kusnendi; Askolani, Askolani; Ciptagustia, Annisa (Fakultas Pendidikan Ekonomi dan Bisnis, 2018)
Universities are organizations with inputs and outputs in the form of human resources so that in achieving quality graduates required quality input. By improving the quality of lecturers and educational staff is a quick way to improve the quality of graduates. In addition, in the process of transformation, organizational support is needed through an organization-focused culture of knowledge. In this case, colleges are trying to optimize what they have to determine the right strategy. Based on our previous research results the commitment of human resources is the factor that most influence the performance of universities. One way that is used is to associate the concept of quality with human resource management as a system of human resource improvement, which is with total quality human resource management (TQHRM). This study aim to develop a performance model of higher education organizations based on TQHRM and Knowledge Strategy. This research use survey method. This research is done at the Universitas Pendidikan Indonesia (UPI) with the subject of research is all academic units consisting of graduates study program which amounts to 71 departments. Because this research develops a model which is more formative then more suitable to use Partial Least Square (SEM-PLS). The result finding in Universitas Pendidikan Indonesia, TQHRM and Knowledge Strategy does not affect the performance of the organization. In using the indicators of organizational performance using balance scorecard in higher education is required assumptions include (1) the clarity and alignment of key performance indicators and performance appraisal university courses, (2) high organizational commitment of his teachers.Â Â Â